New constraints of terrestrial and oceanic global gross primary productions from the triple oxygen isotopic composition of atmospheric CO2 and O2 - Mao-Chang Liang (3225573) (2023)
Representations of the changing global carbon cycle under climatic and environmental perturbations require highly detailed accounting of all atmosphere and biosphere exchange. These fluxes remain unsatisfactory, as a consequence of only having data with limited spatiotemporal coverage and precision, which restrict accurate assessments. Through the nature of intimate coupling of global carbon and oxygen cycles via O2 and CO2 and their unique triple oxygen isotope compositions in the biosphere and atmosphere, greater insight is available. We report analysis of their isotopic compositions with the widest geographical and temporal coverage (123 new measurements for CO2) and constrain, on an annual basis, the global CO2 recycling time (1.5 ± 0.2 year) and gross primary productivities of terrestrial (~ 170–200 PgC/year) and oceanic (~ 90–120 PgC/year) biospheres. Observed inter-annual variations in CO2 triple oxygen isotopic compositions were observed at a magnitude close to the largest contrast set by the terrestrial and oceanic biospheres. The seasonal cycles between the east and west Pacific Ocean were found to be drastically different. This intra-annual variability implies that the entire atmospheric CO2 turnover time is not much longer than the tropospheric mixing time (less than ~ 5 months), verifying the derived recycling time. The new measurements, analyses, and incorporation of other global data sets allow development of an independent approach, providing a strong constraint to biogeochemical models. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-023-29389-z